Digital Public Consultation and the Opportunities for Participatory Democracy: An Exploratory Study - Diana Gabriela Reianu; Dorin Mircea Dobra (Social Sciences)
The decision-making process involves different stages in which the authorities should ensure that citizens’ views and concerns are voiced by encouraging citizens to become directly involved in policy areas and issues so that they can actively engage in collective public choices. Public consultation therefore plays a crucial role in promoting democratic values and strengthening the legitimacy of decision-making processes in governments and organizations. This study aims to analyze young people’s reaction to the general trend towards digitalization and the extent to which young people are willing to adopt new digital methods of public consultation. The results show that the digitalization trend is sparking enthusiasm for innovation and efficiency among our respondents, but they also highlight concerns about data security and the impact on jobs. Our study finds a generally positive attitude towards the use of online platforms for public consultations, highlighting the role of online platforms in increasing the trust of European citizens in the European legislature, but at the same time questioning the importance the European Union would attach to opinions expressed through digital platforms and the representativeness of the group of participants. The results of this study have strong administrative and managerial implications and can provide important insights into the search for solutions regarding the implementation of digitalization and online consultation in EU legislation.